Forecasting large datasets with reduced rank multivariate models - Andrea Carriero; George Kapetanios; Massimiliano Marcellino (Queen Mary University of London, Department of Economics, 2007)
The paper addresses the issue of forecasting a large set of variables using multivariate models. In particular, we propose three alternative reduced rank forecasting models and compare their predictive performance with the most promising existing alternatives, namely, factor models, large scale bayesian VARs, and multivariate boosting. Specifically, we focus on classical reduced rank regression, a two-step procedure that applies, in turn, shrinkage and reduced rank restrictions, and the reduced rank bayesian VAR of Geweke (1996). As a result, we found that using shrinkage and rank reduction in combination rather than separately improves substantially the accuracy of forecasts, both when the whole set of variables is to be forecast, and for key variables such as industrial production growth, inflation, and the federal funds rate.
Keywords: C11; C13; C33; C53; 330; Bayesian VARs; Factor models; Forecasting; Reduced rank; Multivariate Analyse; Prognoseverfahren; Ranking-Verfahren; Bayes-Statistik